ANALISIS INTEGRATIF WAHYU, AKAL, DAN INDRA SEBAGAI SUMBER ILMU PENGETAHUAN - Ahmad Taufiq Hidayatullah; Ahmad Faruq; Maskur Azka; Muhammad Hori (Al Arsy: Journal of Education, Management and Islamic Thought, 2025)
Knowledge is sometimes acquired through divine revelation, reason, and the senses. Revelation serves as the primary source of truth that comes from the Lord of the universe, reason functions to reflect, evaluate, and expand knowledge, and the senses act as empirical instruments to observe and comprehend the signs of God’s greatness in the universe. This study aims to analyze the integration of revelation, reason, and the senses as sources of knowledge based on the Qur’an and Hadith. The research employs a library research method with a thematic approach to Qur’anic verses and the hadiths of the Prophet Muhammad (peace be upon him) related to the acquisition and development of knowledge. The findings indicate that the Qur’an encourages the optimal use of reason and the senses within the framework of revelation, as reflected in commands to think, observe, and draw lessons from nature and the history of past communities. The integration of revelation, reason, and the senses produces a comprehensive framework of knowledge that focuses on truth, usefulness, and the strengthening of faith. This study is expected to contribute conceptually to the advancement of knowledge and Islamic education grounded in the Qur’an and Hadith.